Comparison of Macrophomina phaseolina inoculation techniques for screening sunflower and soybean germplasm in a controlled environment. Issue 6 (2nd November 2021) - Talapov, T.; Yuceer, S.; Dedecan, O.; Demirel, O.; Can, C.
Abstract: Macrophomina phaseolina is a polyphagous phytopathogenic fungus that causes serious yield losses in economically important crop plants. The most appropriate control measure for this fungus is the utilization of resistance sources. To achieve this a fast and reliable screening method, in addition to a characterized pathogen population, is a prerequisite to accelerate breeding programmes. The aim of this study was to develop an efficient inoculation method for soybean and sunflower seedlings and to test the effect of inoculum maturity on disease development under controlled environmental conditions. Three inoculation methods, stem-tape, cut-stem and toothpick, and two inoculum types, hyphal and microsclerotial, were tested on sunflower and soybean seedlings. The fastest disease development on sunflower was obtained with the cut-stem and stem-tape inoculation methods using hyphal inoculum, and both methods had high repeatability. The cut-stem method, however, is not applicable for germplasm screening studies due to the predisposition of sunflower seedlings to pathogen attack. Application of the stem-tape inoculation method was useful for a variety of host reaction studies and for rapid germplasm screening. In soybean, the cut-stem inoculation method yielded consistent results in pathogenicity and variety reaction studies, but the stem-tape and toothpick inoculation methods had poor repeatability and long incubation periods, respectively. The cut-stem method in soybean and the stem-tape method in sunflower appear to be the most appropriate for pathogenicity and rapid germplasm screening studies with M. phaseolina under controlled conditions.